2019
DOI: 10.1158/1078-0432.ccr-19-0733
|View full text |Cite
|
Sign up to set email alerts
|

TFEB Mediates Immune Evasion and Resistance to mTOR Inhibition of Renal Cell Carcinoma via Induction of PD-L1

Abstract: Purpose: Despite the FDA approval of mTOR inhibitors (mTORi) for the treatment of renal cell carcinoma (RCC), the benefits are relatively modest and the few responders usually develop resistance. We investigated whether the resistance to mTORi is due to upregulation of PD-L1 and the underlying molecular mechanism.Experimental Design: The effects of transcription factor EB (TFEB) on RCC proliferation, apoptosis, and migration were evaluated. Correlation of TFEB with PD-L1 expression, as well as effects of mTOR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 36 publications
5
60
0
Order By: Relevance
“…As a result, knockdown of TFEB did not affect cell proliferation. This is consistent with previous report [23]. But interestingly, knockdown of TFE3 signi cantly inhibited cell proliferation ( Fig 1F).…”
Section: Tfe3 But Not Tfeb Affects Cell Proliferation Of Ccrcc Cellssupporting
confidence: 93%
See 4 more Smart Citations
“…As a result, knockdown of TFEB did not affect cell proliferation. This is consistent with previous report [23]. But interestingly, knockdown of TFE3 signi cantly inhibited cell proliferation ( Fig 1F).…”
Section: Tfe3 But Not Tfeb Affects Cell Proliferation Of Ccrcc Cellssupporting
confidence: 93%
“…Identi cation the TFE3 regulated genes in ccRCC cells can provide better understanding of TFE3 functions in the regulation ccRCC tumorigenesis and the interaction between ccRCC cells and the immune microenvironment. Recent study showed that TFEB can mediate immune evasion by positively regulation the expression of PD-L1 in RCC [23]. Given the similar roles of TFE3 and TFEB in the crossregulation of cellullar functions, we tested the expression of typical immune checkpoints, and interestingly we found that TFE3 can also regulate the expression of many immune checkpoints including CD273 (PD-L2) CD274 (PD-L1) CD275 (ICOSL) and CD270 (HVEM).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations